The Competitiveness Of Micro Small And Medium Enterprises In The Tourism Sector: The Role Of Social Capital And Innovation - Arie F. Kawulur; Tinneke E.M. Sumual; Nikolas F. Wuryaningrat (AIBPM Publisher, 2025)
The competitiveness among Micro, Small, and Medium Enterprises (MSME) remains an important issue for stakeholders among various sectors. Unfortunately, businesses in the tourism sector have received less attention, particularly in terms of the social capital and innovation. Therefore, this study aims to analyze the relationship between social capital and innovation and their impact on the competitiveness of micro, small, and medium enterprises in Indonesia’s super-priority tourism areas. Using a sample of 40 enterprises, the study reveals that dimensions of social capital, namely trust, networks, and norms, along with innovation, contribute significantly to fostering competitiveness. Furthermore, networks play a crucial role in driving innovation within micro, small, and medium enterprises in the tourism sector. This research provides valuable insights for policymakers in fostering a more sustainable business climate, particularly by emphasizing the importance of social capital and innovation in enhancing MSME competitiveness.